2006
DOI: 10.1080/00016340500408325
|View full text |Cite
|
Sign up to set email alerts
|

The effect of accelerated rehabilitation on recovery after surgery for ovarian malignancy

Abstract: The concept of fast-track multimodal rehabilitation appears to be beneficial in patients operated for ovarian malignancy, as hospital stay and medical morbidity are reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 16 publications
3
70
0
2
Order By: Relevance
“…Our study group consisted mostly of a group of low-risk endometrial cancers (FIGO stage 1) or early ovarian cancer, for which our national guidelines recommend this less-extensive surgery. We cannot therefore say anything directly about the outcome after more extensive surgery, but there are also some data from other studies suggesting the same benefit in this group [7,10]. In addition, patients who have undergone more extensive surgery would probably benefit equally or even more from stress reduction.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Our study group consisted mostly of a group of low-risk endometrial cancers (FIGO stage 1) or early ovarian cancer, for which our national guidelines recommend this less-extensive surgery. We cannot therefore say anything directly about the outcome after more extensive surgery, but there are also some data from other studies suggesting the same benefit in this group [7,10]. In addition, patients who have undergone more extensive surgery would probably benefit equally or even more from stress reduction.…”
Section: Discussionmentioning
confidence: 89%
“…The reasons for not including patients with malignant disease in these early studies have not been stated. Some of the more recent studies have used fast-track or ERAS protocols in patients with malignant disease who have undergone various types of gynecological surgeries [7,8,9,10], all with the same conclusion of achieving shorter LOS and enhancing recovery. These studies included prospectively collected data in ERAS-treated patients compared with historical controls, or were performed retrospectively.…”
Section: Introductionmentioning
confidence: 99%
“…This study has demonstrated that with experience, 1 in 3 patients undergoing a laparotomy for gynaecological surgery can be discharged on day 2 post surgery, without an increased morbidity or readmission rate [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…(Marx, 2006& Jakobsen, 2010 The first of these, published in Acta Obstetricia et Gynecologica in 2006, was a case control study involving a total of 141 women. One group (comprising 72 women) received conventional care and were analysed retrospectively whilst the second group (69 women) received multimodal rehabilitation and were studied prospectively.…”
Section: Discussionmentioning
confidence: 99%
“…The next study examined at was 'The effect of accelerated rehabilitation on recovery after surgery for ovarian malignancy' by Marx et al (Marx, 2006) This was a case control study looking at surgery for ovarian malignancy (undertaken according to guidelines from the International Federation of Gynecology and Obstetrics). A total of 141 women were included: 72 patients receiving conventional perioperative care were compared with 69 patients receiving multimodal, fast-track rehabilitation.…”
Section: Enhanced Recovery After Surgery With Reference To Hysterectomymentioning
confidence: 99%